2018
DOI: 10.1021/acs.jafc.8b00660
|View full text |Cite
|
Sign up to set email alerts
|

Can Glycation Reduce Food Allergenicity?

Abstract: As a naturally occurring reaction during food processing, glycation, also known as non-enzymatic browning or Maillard reaction, can improve food protein physiochemical properties and functionality. In this perspective, three aspects of glycation (terminology confusion between glycation and glycosylation, its current application, and its impact on immunoreactivity) are elaborated. Overall, the immunoreactivity of glycated proteins may decrease, remain unchanged, or even increase after food glycation. Also, it s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
1
15
0
1
Order By: Relevance
“…A recent review reported that glycation is an effective way to reduce the allergenicity of some food proteins (Rao, Jiang, Li, Samiwala, & Labuza, 2018). Indeed, glycation was found to reduce the IgE-binding ability of ovalbumin but not ovomucoid.…”
Section: Glycationmentioning
confidence: 99%
“…A recent review reported that glycation is an effective way to reduce the allergenicity of some food proteins (Rao, Jiang, Li, Samiwala, & Labuza, 2018). Indeed, glycation was found to reduce the IgE-binding ability of ovalbumin but not ovomucoid.…”
Section: Glycationmentioning
confidence: 99%
“…These results may be due to the exposure of interior epitopes of OVM during deglycosylation and the generation of glycation products, which could function as potent epitopes (Toda et al., 2014). Conversely, the IgE‐binding abilities of OVM‐FOS and OVM‐GOS decreased because of the mask of the epitopes of OVM by glycation (Rao et al., 2018). Besides, the IgE‐binding capacity of OVM‐FOS was stronger than that of OVM‐GOS, showing the decrease of IgE‐binding capacity of glycated OVM with the increase of its glycation degree.…”
Section: Resultsmentioning
confidence: 99%
“…(2019) found that deglycosylation can enhance the allergenicity of shrimp tropomyosin. Besides, the effects of glycation on the allergenicity of allergenic proteins are heavily dependent upon the kinds of saccharides (Rao et al., 2018). Glycation can not only weaken the allergenicity of allergenic proteins through destroying and masking epitopes but also enhances the allergenicity of allergenic proteins via the generation of glycation products as new potent epitopes (Mueller et al., 2013; X. Zhu & Lin, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, trypsin hydrolysis generated two polypeptide fragments from cod that are allergenic [ 128 ]. Glycation, as another food processing method, could also increase or protein allergenicity [ 129 ]. After glycation, the digestibility and allergenicity of carp parvalbumin increased and decreased, respectively, due to glucose attachment to IgE epitopes [ 122 ].…”
Section: Effect Of Processing On Fish Allergensmentioning
confidence: 99%